Evaluating the effects between metal mixtures and serum vaccine antibody concentrations in children: a prospective birth cohort study - Barrett M. Welch; Adam Branscum; G. John Geldhof; Sharia M. Ahmed; Perry Hystad; Ellen Smit; Sakila Afroz; Meghan Megowan; Mostofa Golam; Omar Sharif; Mahmuder Rahman; Quazi Quamruzzaman; et al. (BMC, 2020)
Abstract Background Many populations are exposed to arsenic, lead, and manganese. These metals influence immune function. We evaluated the association between exposure to single and multiple metals, including arsenic, lead, and manganese, to humoral immunity as measured by antibody concentrations to diphtheria and tetanus toxoid among vaccinated Bangladeshi children. Additionally, we examined if this association was potentially mediated by nutritional status. Methods Antibody concentrations to diphtheria and tetanus were measured in children's serum at age 5 (n = 502). Household drinking water was sampled to quantify arsenic (W-As) and manganese (W-Mn), whereas lead was measured in blood (B-Pb). Exposure samples were taken during pregnancy, toddlerhood, and early childhood. Multiple linear regression models (MLRs) with single or combined metal predictors were used to determine the association with antibody outcomes. MLR results were transformed to units of percent change in outcome per doubling of exposure to improve interpretability. Structural equation models (SEMs) were used to further assess exposure to metal mixtures. SEMs regressed a latent exposure variable (Metals), informed by all measured metal variables (W-As, W-Mn, and B-Pb), on a latent outcome variable (Antibody), informed by measured antibody variables (diphtheria and tetanus). Weight-for-age z-score (WFA) at age 5 was evaluated as a mediator. Results Diphtheria antibody was negatively associated with W-As during pregnancy in MLR, but associations were attenuated after adjusting for W-Mn and B-Pb (− 2.9% change in diphtheria antibody per doubling in W-As, 95% confidence interval [CI]: − 7%, 1.5%). Conversely, pregnancy levels of B-Pb were positively associated with tetanus antibody, even after adjusting for W-As and W-Mn (13.3%, 95% CI: 1.7%, 26.3%). Overall, null associations were observed between W-Mn and antibody outcomes. Analysis by SEMs showed that the latent Metals mixture was significantly associated with the latent Antibody outcome (β = − 0.16, 95% CI: − 0.26, − 0.05), but the Metals variable was characterized by positive and negative loadings of W-As and B-Pb, respectively. Sex-stratified MLR and SEM analyses showed W-As and B-Pb associations were exclusive to females. Mediation by WFA was null, indicating Metals only had direct effects on Antibody. Conclusions We observed significant modulation of vaccine antibody concentrations among children with pregnancy and early life exposures to drinking water arsenic and blood lead. We found distinct differences by child sex, as only females were susceptible to metal-related modulations in antibody levels. Weight-for-age, a nutritional status proxy, did not mediate the association between the metal mixture and vaccine antibody.